Free‐Standing Holey Ni(OH)2 Nanosheets with Enhanced Activity for Water Oxidation. Issue 26 (19th May 2017) - Kong, Xiangkai; Zhang, Changlin; Hwang, Sang Youp; Chen, Qianwang; Peng, Zhenmeng
Abstract : Electrochemical water oxidation is the key technology in water‐splitting reactions and rechargeable metal–air batteries, which is very attractive for renewable energy conversion and storage. Replacement of precious catalysts with cost‐effective and highly active alternatives is still a great challenge. Herein, based on theoretical predictions, holey structures are designed and fabricated on the free‐standing conventional 2D OER catalyst. By well‐controlled defects engineering, uniform tiny holes are created on the free‐standing Ni(OH)2 nanosheets via a sol–gel method, with the embedded Zn components as the template for holes production. The whole preparation process is feasible and effective to make full use of the basal plane of 2D nanomaterials, which can provide higher surface area, richer defects, more grain boundaries, and edge sites, as well as greater distorted surfaces. Meanwhile, these holes developed inside the sheet structure can supply tremendous permeable channels for ions adsorption and transportation, enable a fast interfacial charge transfer and accelerate the reaction process. The as‐prepared 2D holey Ni(OH)2 nanostructures exhibit excellent catalytic performance toward electrochemical water oxidation, with lower onset overpotentials and higher current densities compared with the pristine Ni(OH)2 catalyst, suggesting the holey defects engineering is a promising strategy for efficient water‐splitting devices and rechargeable metal–air batteries. Abstract : Based on theoretical calculations, uniform tiny holes are designed and created on free‐standing holey Ni(OH)2 nanosheets via a feasible sol–gel method, which can further make full use of the 2D nanostructures. The enhanced electrochemical water oxidation abilities are observed, demonstrating the advances of holey structures produced on the inorganic 2D nanomaterials.